Kidney transplantation, bioengineering, and regeneration kidney transplantation in the regenerative medicine era (Academic Press, an imprint of Elsevier, 2017)
Kidney Transplantation, Bioengineering, and Regeneration: Kidney Transplantation in the Regenerative Medicine Era investigates how the field of regenerative medicine is changing the traditional premises of solid organ transplantation, specifically within the field of kidney transplantation